Housing equity for health equity: a rights-based approach to the control of Lassa fever in post-war Sierra Leone - Kelly J Daniel; Barrie M Bailor; Ross Rachel A; Temple Brian A; Moses Lina M; Bausch Daniel G (BMC, 2013)
Abstract Poor quality housing is an infringement on the rights of all humans to a standard of living adequate for health. Among the many vulnerabilities of those without adequate shelter is the risk of disease spread by rodents and other pests. One such disease is Lassa fever, an acute and sometimes severe viral hemorrhagic illness endemic in West Africa. Lassa virus is maintained in the rodent Mastomys natalensis, commonly known as the "multimammate rat," which frequently invades the domestic environment, putting humans at risk of Lassa fever. The highest reported incidence of Lassa fever in the world is consistently in the Kenema District of Sierra Leone, a region that was at the center of Sierra Leone's civil war in which tens of thousands of lives were lost and hundreds of thousands of dwellings destroyed. Despite the end of the war in 2002, most of Kenema's population still lives in inadequate housing that puts them at risk of rodent invasion and Lassa fever. Furthermore, despite years of health education and village hygiene campaigns, the incidence of Lassa fever in Kenema District appears to be increasing. We focus on Lassa fever as a matter of human rights, proposing a strategy to improve housing quality, and discuss how housing equity has the potential to improve health equity and ultimately economic productivity in Sierra Leone. The manuscript is designed to spur discussion and action towards provision of housing and prevention of disease in one of the world's most vulnerable populations.